Accountant bags AeU's Chairman Award - The, Sun (the sun, 2014)
In the 4th Convocation ceremony has awarded Chairman award to deserving graduate, Chow Choi Chin who graduated with Master of Education. According to how Choi Chin " the most challenging task was striking a balance between work, family and studies."